Vibrational spectroscopy for characterisation of a cyclic antimicrobial peptide - Pfukwa, Ngaatendwe Buhle Cathrine (Stellenbosch : Stellenbosch University, 2021)
Thesis (PhD)--Stellenbosch University, 2021.